Pariwisata dan Perubahan Persepsi atas Hutan di Kawasan Taman Nasional Bromo Tengger Semeru - Perkasa, Andika Nur (Journal of Indonesian Tourism and Policy Studies, 2016)
This paper examines the implication on growing interest of tourist on kind of travel nature in Bromo Tengger Semeru National Park (TNBTS) for the Tenggernese who live in enclave area TNBTS. This study is prioritized on public perception of forests as the main attraction to tourist to visit. Dwelling perspective used to announce process establishing a perception of forest from the various actors and related actions. The establishing process of forest perception cannot be separated from space forest history formation by the government, either its function or ownership. This study then using conjuncture analysist prioritized on the life space aspect. The result of this study indicates a shift in perception of forest for the community due to the tendency of government to make tourism as a source of sustainable income not for conservation purposes.